The role of glucocorticoids in erythropoiesis - Hanssen, Lars L. P.; Iskander, Deena (Frontiers in Hematology, 2025)
Erythropoiesis is a critical homeostatic process responsible for the production of red blood cells, essential for oxygen delivery to tissues. This review provides a brief overview of erythropoiesis: the maturation of hematopoietic stem cells to circulating red blood cells. We examine the role of glucocorticoids (GCs) in modulating this process, highlighting how they influence erythroid progenitor proliferation and differentiation through various mechanisms, including transcriptional repression and non-genomic pathways. GCs have been shown to inhibit erythroid differentiation while promoting progenitor cell expansion, particularly under stress conditions such as anaemia or blood loss. These mechanisms are likely central to understanding the role of GC signalling in the treatment of haematological diseases such as Diamond-Blackfan anaemia syndrome and myelodysplastic syndromes, emphasising the need for further research into the genetic and epigenetic factors affecting individual responses to glucocorticoid therapy. By elucidating the intricate interplay between GCs and erythropoiesis, this work aims to provide insights into potential therapeutic strategies for managing disorders related to red blood cell underproduction.